Antepartum Cardiotocography and Feto-maternal Outcome Among Admitted Patients in Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka, Bangladesh (IAHS Medical Journal, 2024)
Background: Admission Cardiotocography (CTG) a noninvasive procedure, is used to indicate the state of oxygenation of the fetus on admission into the labor ward. This study is performed to assess the association of admission CTG findings with feto-maternal outcome at a tertiary health facility in Bangladesh.Materials and methods: A prospective, observational study of 50 pregnant women who were admitted into the labor ward with singleton live pregnancies in Bangabandhu Sheikh Mujib Medical University. Information on the demographic characteristics, obstetrics and medical history, admission CTG tracing and neonatal outcome was obtained using a structured data collection form. Data were analyzed using the SPSS software version 20.0 with the level of significance set at p< 0.05.Results: The admission CTG findings were normal in 72% and abnormal in 28% of the women. The occurrence of low birth weight, asphyxiated neonates and Special Care Neonatal Unit (SCANU) admission was significantly more frequent among those with abnormal admission CTG results compared with normal results (p